THE EFFECT OF NON-PERFORMING LOANS AND LOAN DEPOSIT RATIOS ON STOCK RETURNS IS MEDIATED BY A PROFITABILITY STUDY ON COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2016 - 2018 - Iskandar, Yusuf; Suharyanto, Suharyanto; Zaki, Achmad; Widhayani, Puri Setioningtyas (Jurnal Aplikasi Manajemen, 2023)
Stock return is an indicator of banking performance in Indonesia. This study aims to empirically test non-performing loans and loan deposit ratios on stock returns mediated by return on assets at commercial banks listed on the Indonesian stock exchange in 2016-2018. The sample used in this study was 20 bank companies that met predetermined criteria. The data that has been collected is then analyzed using Path analysis to test the proposed hypothesis. The findings of this study indicate that non-performing loans and loan deposit ratios each have a significant effect on stock returns and are mediated by return on assets. Based on these findings, it is recommended that banking companies, in managing financial ratios, must run more optimally to maximize stock returns obtained by banks. Non-performing loan, loan deposit ratio is a bank's financial ratio to assess its performance. These financial ratios have a purpose to determine the bank's ability to optimize the level of lending to the public, generate profits from the activities carried out and reject the risks from its operational activities. For banking companies, the findings of this study can be used in policy-making related to the delivery of information on bank performance reports to investors.